Brain Injury Impairs Working Memory and Prefrontal Circuit Function - Smith, Colin J.; Xiong, Guoxiang; Elkind, Jaclynn A.; Putnam, Brendan; Cohen, Akiva S. (Frontiers in Neurology, 2015)
More than 2.5 million Americans suffer a traumatic brain injury (TBI) each year. Even mild to moderate traumatic brain injury causes long-lasting neurological effects. Despite its prevalence, no therapy currently exists to treat the underlying cause of cognitive impairment suffered by TBI patients. Following lateral fluid percussion injury (LFPI), the most widely used experimental model of TBI, we investigated alterations in working memory and excitatory/inhibitory synaptic balance in the prefrontal cortex. LFPI impaired working memory as assessed with a T-maze behavioral task. Field excitatory postsynaptic potentials recorded in the prefrontal cortex were reduced in slices derived from brain-injured mice. Spontaneous and miniature excitatory postsynaptic currents onto layer 2/3 neurons were more frequent in slices derived from LFPI mice while inhibitory currents onto layer 2/3 neurons were smaller after LFPI. Additionally, an increase in action potential threshold and concomitant decrease in firing rate was observed in layer 2/3 neurons in slices from injured animals. Conversely, no differences in excitatory or inhibitory synaptic transmission onto layer 5 neurons were observed; however, layer 5 neurons demonstrated a decrease in input resistance and action potential duration after LFPI. These results demonstrate synaptic and intrinsic alterations in prefrontal circuitry that may underlie working memory impairment caused by TBI.